Preparation, electrochemistry and optical properties of unsymmetrical phthalocyanines bearing morpholine and tert-butylphenoxy substituents - Burat, Ayfer Kalkan; Koca, Atıf; Lewtak, Jan P.; Gryko, Daniel T.; Kalkan, Burat Ayfer (Elsevier BV, 2011)
Abstract The synthesis of novel, unsymmetrical, octasubstituted metal-free and metallophthalocyanines (zinc, cobalt) bearing one chlorine, one morpholine moieties and six 4- tert -butylphenoxy substituents was achieved by a statistical condensation reaction of two corresponding phthalonitriles. The new compounds have been characterized by using elemental analyses, UV–vis, IR, 1 H NMR and mass spectroscopic data. Voltammetric and spectroelectrochemical studies are in harmony with the reported metallophthalocyanine complexes, which support the proposed structure of the complexes.